Saúde mental, cidadania e sistemas locais : a experiencia de Santos - Ramos, Ana Maria Lana (1996)
The present study is a reflection over the issue of mental health and the policies developed around this subject in Brazil, foccussing on the Mental Health Program developed in the city of Santos (SP), since 1989. The approach taken in Santos and suggested by the Panamerican Health Organization and by the World Health Organization is comprised of developing the person/society relationship, through the substituition of the hospital centered model by outpatient clinicaI procedures, working fronts, replacement projects and enhancement of the patient in the society. Thus, the issue of mental health is considered, above alI, as a political question, implicating the type of relantionship that society wants to settle with a part of its members. Therefore, it remains circunscribed to the discussion on the social relationships of power and to the build-up of the citizenship in the brazilian contexto